Attitudes of Preschool1 Teachers in Northern Greece on Children and TV Viewing. Issue 3 (September 2013) - Theodosiadou, Sophia; Markos, Angelos
THE PRESENT STUDY EXPLORES views and attitudes of preschool teachers on the role of television in the life of preschool children by investigating the effects of TV viewing on the behaviour of preschoolers and the procedure of learning. A structured questionnaire was used to select opinions and views of 231 preschool teachers in the region of Central Macedonia in Northern Greece. Descriptive statistics and data analysis were performed with SPSS. The analysis revealed that preschool teachers have chiefly negative attitudes towards the effects of TV viewing on the behaviour and everyday life of preschool children and surprisingly these attitudes and views were the same among preschool teachers with different years of teaching experience.